Implementasi Program Kalimasada dalam Tertib Adminduk di Kelurahan Benowo Kecamatan Pakal Kota Surabaya - Risty, Arindra Saskia Maya; Prathama, Ananta (VISA: Journal of Vision and Ideas, 2024)
Population Administration is a very important thing in the life of a country. If people are orderly in population administration then all matters in population administration will be very easy, otherwise if it is not orderly it will be the opposite. Orderly Administering also has a big influence on the country. If the community has orderly administration then all governance processes will always be easy. Unfortunately, in Indonesia, most people are not orderly in Adminduk. Therefore, the government issued the Kalimasada Program or Adminduk Aware Community Environmental Area. One of them, Benowo Village, with a fairly dense population, has been successful in implementing the Kalimasada Program, 85% of which has been completed. This research aims to find out how the implementation of the Kalimasada Program in Benowo Village is said to be successful. This research is a qualitative descriptive research, and the location of this research was carried out in Benowo Village, Pakal District, Surabaya City. Based on the research results, it can be seen that the Kalimasada Program has been considered successful in being implemented in Benowo Village. With house-to-house surveys and interviews, this program can be implemented more quickly among residents. Many residents have carried out renewal and registration of administrative documents such as renewing family cards, making birth certificates and death certificates, making KIA and new records. With the assistance of supporting actors, namely MSib intern students, Head/Mrs. RT, KSH, and sub-district officers. It is hoped that with the running of this program the public will become more aware of the importance of parent administration and always updating the data.